Academic Distress Against Academic Procrastination: Study Analysis of Thesis Completion of Makassar Tourism Polytechnic Students and the Faculty of Psychology, Makassar State University - Siti Fatimah Awalyah Rijal; Ahmad Ridfah; Nur Akmal; Syamsu Rijal (Politeknik Pariwisata Makassar, Indonesia, 2022)
Academic distress is indicated to be the cause of students doing academic procrastination in the preparation of their thesis or final projects. This study uses correlational quantitative methods to determine whether there is an effect of academic distress on academic procrastination. This study involved two groups of samples, cinsists of students of the Faculty of Psychology, Makassar State University (N1=164) and the Makassar Tourism Polytechnic (N2=53) who were preparing a thesis or final project selected using accidental sampling technique. Data obtained through a questionnaire by adopting a Likert scale. The results showed that the hypothesis proposed in this study was accepted, that is, there is a positive and significant influence between academic distress on academic procrastination in students who are writing thesis of fonal project.